Influence of perceive social support or pre-operative support program on quality of life in patients awaiting coronary artery bypass grafting (CABG) surgery: mixed method systematic review - Chong, Mei Chan; Sumaiyah Jamaludin, Thandar Soe (IIUM Press, 2019)
Objective: This paper is a report of a review to identify relevant literature and to summarize the effectiveness of perceived social support on quality of life in patients while waiting for CABG surgery. Background: Cardiovascular disease is one of the most common leading causes of death in the world and the most common treatment is CABG surgery. Patients who has been diagnosed and listed for CABG surgery should adapt himself to overcome the changes in their new life style. To conquer this, they should have social support or pre-operative support while awaiting for their CABG surgery. Data Source: A search of health and health science database located eleven papers including quantitative and qualitative studies focusing on the perceived social support or pre-operative program on quality of life in patients awaiting for CABG surgery. Review Methods: A mixed-method systematic review involving quantitative and qualitative research findings. Inclusion criteria for this review were quantitative and qualitative studies which focus on perceived social support or preoperative program on quality of life in patients awaiting for coronary artery bypass grafting (CABG) surgery. Results: The issue of perceived social support of patients prior to undergoing their CABG surgery existed from last decades. Although many researchers have been conducted studies to solve the said issue, but no proper solution was found till present. Conclusion: More efforts should be made to improve the quality of life in patients awaiting CABG surgery to prepare them physically, mentally and sociologically to adapt themselves to a new life style.